CityPro: city-surveillance collaborative platform. (2017) - Dbouk, Mohamed; Mcheick, Hamid; Sbeity, Ihab
Day by day, modern cities face a big challenge in terms of public safety and security. In the city, the surveillance systems mostly use video surveillance techniques, they incorporate thousands of cameras and relay to high-speed networking infrastructures. Moreover, in a city, there exist multiple computerised standalone systems that operate independently each other, e.g., banking systems, customs, and hospitals. These systems generate huge datasets. The collected data stimulate a gigantic mine of scattered information. A smart city is a city that intelligently benefits from such omnipresent systems. This paper presents an integrated platform to gather multiple existing systems in a city. The platform consists of a collaborative surveillance system, called CityPro. The proposed architecture is intended to protect and monitor people and public infrastructures, such as bridges, roads, buildings, etc.; it is designed to deal with and prevent abnormal activities like terrorist attacks. CityPro is expected to operate in live-mode by using the city digital-infrastructures. At the end of this paper, a typical case study is given, and challenges and future works are also discussed.